Correlation Between Serum Testosterone Levels and CD4 T Lymphocyte Counts in Naive HIV-Infected Men at dr. Mohammad Hoesin General Hospital Palembang - Fahrenheit, Fahrenheit; Kusnadi, Yulianto; Hudari, Harun; Bahar, Erial; Shahab, Alwi; Anggraini, Ratna Maila Dewi; Permata, Mega; Salim, Nelda Aprilia; Yuniza; Bakrie, Muhammad (Clinical and Research Journal in Internal Medicine, 2025)
Background: HIV infection often leads to endocrine complications, including hypogonadism which characterized by low serum testosterone, potentially affects quality of life and contributes to metabolic issues, such as muscle weakness, depression, osteoporosis, and cardiovascular disease. Some studies have indicated a connection between testosterone levels and CD4 T lymphocyte counts.   Aim: To evaluate the correlation between total serum testosterone levels and CD4 T lymphocyte counts in naive HIV-infected men. Methods: A cross-sectional analitycal study was conducted at Dr. Mohammad Hoesin General Hospital, Palembang, from April to October 2024. Involving 64 naive HIV-infected men. Total serum testosterone and CD4 T cell counts were measured and analyzed. Results: Participants mean age is 36.52 ± 11.03 years with BMI of 19.52 ± 3.71 kg/m². Most subject (62.5%) are reported men who had sex with other men. Poor sleep quality was found in 81%, mild depressive symptoms in 38.1%, and mild erectile dysfunction in 28.6%. Hypogonadism occurred in 32.8% of subjects (28.1% secondary and 4.7% primary). Mean number of testosterone level was 446.75 ± 260.95 ng/dL, with a median CD4 count of 23.5 cells/µL. A significant positive correlation was observed between testosterone levels and CD4 counts (r = 0.313; p = 0.012) although testosterone levels did not significantly differ across HIV clinical stages (p = 0.464). Conclusion: There is a significant positive correlation between serum testosterone levels and CD4 T lymphocyte counts in naive HIV-infected men. Hormonal disturbances may arise in early infection. Hence, testosterone assessment is recommended during the initial evaluation on HIV patients.